Determination of the Width of the Top Quark - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Malik, S.; et al. (Amer Physical Soc, 2011)
We extract the total width of the top quark, Gamma(t), from the partial decay width Gamma(t -> Wb) measured using the t-channel cross section for single top-quark production and from the branching fraction B(t -> Wb) measured in t (t) over bar t events using up to 2.3 fb(-1) of integrated luminosity collected by the D0 Collaboration at the Tevatron p (p) over bar Collider. The result is Gamma(t) = 1.99(-0.55)(+0.69) GeV, which translates to a top-quark lifetime of tau(t) = (3.3-(+1.3)(0.9)) x 10(-25) s. Assuming a high mass fourth generation b' quark and unitarity of the four-generation quark-mixing matrix, we set the first upper limit on vertical bar V-tb'vertical bar < 0.63 at 95% C.L.